Apostila em Visual Law como alternativa à audiência admonitória: um estudo de caso de projeto implementado na 1ª Vara Federal da Subseção Judiciária de Ponta Grossa/Pr - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This dissertation examines the intersection between Law and Visual Communication through a case study of the project "Do You Know Who You're Talking To?" implemented in the 1st Court of the Judicial Subsection of Ponta Grossa/PR (PRPGO01). This project involves the implementation of a Visual Law booklet as an alternative to admonitory hearings in Criminal Enforcement processes. The central objective of this research is to address the hypothesis: does the Visual Law booklet as an alternative to admonitory hearings in Criminal Enforcement processes optimize access to justice from a usability perspective? The study employs a methodological approach that combines qualitative and quantitative analyses, including literature review, document analysis, interviews with judges and court staff, and questionnaires with lawyers. It assesses whether the Visual Law booklet, sent along with the summons for sentence enforcement in criminal enforcement processes, can simplify legal procedures and offer a more efficient solution in terms of usability, particularly concerning the elimination of the need for admonitory hearings. Structurally, the first chapter of this work addresses the methodological aspects, with special emphasis on the research classification and the methods used for data collection and analysis. The second chapter is focused on the case study of the project implemented in PRPGO01, within the context of the Brazilian criminal enforcement process. The third chapter is dedicated to the qualitative study of the project's implementation, conducted through a critical and systematic approach to the data obtained from interviews with judges and court staff, as well as questionnaires with lawyers. The collected data reveal that the summons accompanied by the booklet facilitated the understanding and compliance with final criminal sentences, significantly reducing the number of queries and the need for new summonses. However, the same data indicate the need for continuous evolution of the model to better balance technological efficiency with the humanization of the judicial process.
Keywords: Visual law na execução penal; Justiça penal 4.0; Execução penal 4.0; Acesso à justiça otimizada; Otimização do acesso à justiça; Visual Law in Criminal Execution; Criminal Justice 4.0; Criminal Execution 4.0; Optimized Access to Justice; Optimization of Access to Justice; CNPQ::CIENCIAS SOCIAIS APLICADAS